Personalized Medicine, in Relation to Redox State, Diet and Lifestyle - Atroshi, Faik (IntechOpen, 2020)
"Personalized Medicine, in Relation to Redox State, Diet and Lifestyle" is a book on the important issues regarding good health and a need for more selective and sensitive systems to identify diseases. It is a complex issue. Presently, in 2020 we have the fight against Coronavirus with high lethality and the world is asking for information on its metabolism, spread and tools to prevent, protect and cure. The complexity of diseases indicate that we must involve diet and lifestyle at the individual level and discuss the possible impact on evolutionary defense systems. We also need to include discussions of the redox state of compounds and this requires collaborations between research areas. The book has gathered interdisciplinary works, joining fields such as trace elements, biochemistry, physiology and analytical chemistry with the aim of finding new approaches to diseases, for example by using individual treatment at the cellular level.